Rule modification in junior sport: Does it create differences in player movement? - Gastin, P. B.; Allan, M. D.; Bellesini, K.; Spittle, M. (Journal of Science and Medicine in Sport, 2017)
Objectives: To determine the effects of rule modification on player movement during matchplay in junior Australian football (AF). Design: Quasi-experimental study design. Methods: Time-motion analysis was used to record variables pertaining to player movement including total distance covered, high-speed running (HSR) distance (>14.4 km/h) and HSR efforts. GPS data obtained from 145 players (7-12 years) were analysed across four junior AF leagues and three age group combinations (U8/U9, U9/U10 and U11/U12). The four leagues were collapsed into two separate conditions (compliant and non-compliant) based on their adherence to a modified junior sport policy. To control for the influence of age and physical maturity, a secondary analysis was performed on an adequately matched U8 subset of data (n = 48). Results: Significant differences (p < 0.05) were found between compliant and non-compliant leagues for age and all player movement variables, with participants in the compliant leagues achieving less player movement. Significant differences were also evident between conditions in the U8 subset in total and relative distance and HSR efforts, with moderate to very large differences (29-60%) observed for all player movement variables. Conclusions: Rule modifications limits the extent and intensity of player movement in junior AF compared to standard playing conditions. The unintended effect of reduced physical activity with rule modifications should be compensated for with additional activities wherever possible. League administrators and policy makers should consider the objectives of rule modifications and weigh up both positive and negative outcomes.